Nuclear Risks in Northeast Asia: Opportunities and Challenges for Extended Deterrence and Assurance - Brian Radzinsky (Journal for Peace and Nuclear Disarmament, 2018)
In February 2018, the Carnegie Endowment for International Peace and Nagasaki University convened a conference on Nuclear Risks in North East Asia. The conference addressed two sources of nuclear risk in the region. North Korea’s nuclear and ballistic missile capabilities present new challenges to U.S. extended deterrence commitments to Japan and South Korea. How the US, Japan, and South Korea coordinate responses to these challenges will affect the future credibility of their alliances. The allies must navigate complex interests surrounding potential augmentation of military capabilities to deter North Korea, the specific role of US nuclear weapons in strengthening extended deterrence, adapting alliance consultation mechanisms, and broader political and economic issues that affect perceptions of the health of the alliances. A second potential source of risk is Japan’s plutonium stockpile, which may grow further in the future, and the possibility that China and South Korea may also embark on reprocessing programs. There is considerable disagreement over the potential for these developments to exacerbate regional and global proliferation risks, although it remains unlikely that Japan will divert plutonium for military purpose. A range of measures, including unilateral and cooperative approaches, have been proposed to mitigate the risks, although entail significant challenges or limitations.